Optimization of Parameters in WEDM Using CCF Design - P., Bharathi.; G., Srinivasara; P., Gopalakrishnaiah (International Journal of Engineering and Technology, 2018)
The research work is to investigate the influence of WEDM process parameters such as pulse on time(Ton),pulse off time(Toff), peak current (IP), servo voltage (SV), and wire feed (WF) on response parameters as Material Removal Rate (MRR), Surface roughness(SR). Experimentation work carried out on Titanium 5 Grade work material with tool electrode as annealed brass wire.  Every process parameter was set at three levels and the output variables were Surface roughness (SR) and Material removal rate (MRR). Central Composite Face centered (CCF) design was used to conduct the experiments. According to the experimental results the model equations for SR and MRR were developed using multiple linear regression.  Modeling and optimization of process parameters had been performed with the help of model equations, level means and response graphs. From the analysis it was identified that the effect of servo voltage on surface roughness  and pulse on time for  MRR is more significant.